The Effect of Service Quality on Employee Performance and Customer Satisfaction at PT. PBM Adhiguna Putera - Zahara Ainaya Asmaralda; Chandra Wijaya (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
This research examines the effect of service quality on employee performance and customer satisfaction at PT PBM Adhiguna Putera. As a maritime transportation and logistics company, PT PBM Adhiguna Putera faces challenges in improving service quality and customer satisfaction in the post-COVID-19 era. This research aims to analyze the relationship between service quality, employee performance, and customer satisfaction, as well as to examine the mediating role of employee performance in this relationship. The research employs a quantitative approach with a descriptive design. Data collection was conducted through a survey of 75 consumers and in-depth interviews with key stakeholders. Data analysis was performed using SPSS and SmartPLS to measure the strength of relationships between variables based on the research's structural model. The findings indicate that service quality has a positive and significant effect on employee performance (coefficient 0.790; p-value 0.000) and customer satisfaction (coefficient 0.903; p-value 0.000). Additionally, employee performance positively influences customer satisfaction (coefficient 0.412; p-value 0.038). The mediation analysis reveals that employee performance mediates the relationship between service quality and customer satisfaction, with a coefficient of 0.326 and a p-value of 0.029. The implications of this research emphasize the importance of improving service quality and human resource management as key strategies for enhancing company performance. The findings can serve as a foundation for PT PBM Adhiguna Putera in designing more effective policies to improve customer satisfaction through the enhancement of employee performance.